Elucidating the N-N and C-N Bond-breaking Mechanism in the Photoinduced Formation of Nitrile Imine - Ayarde Henriquez, Leandro (My University, 2023)
In this study, we revealed the significance of chemical bonding for the photochemically induced mechanism of 2-phenyl tetrazole derivatives generating nitrile imines. The correlated electron localization function shows that the formation of imine nitrile involves two key bond events: (i) the heterolytic C-N breakage taking place in the T1 state and (ii) the homolytic N-N rupture occurring in the T2 excited state. In particular, a cation-radical specie results from the C-N cleavage, whereas the N-N rupture creates a biradical resonant form of imine nitrile. Additionally, we noticed that the substantial pair delocalization of the C-C-N bonded structure could play a significant role in the conversion of the biradical imine nitrile into both the propargylic and allenic forms via the T1 →S0 deactivation.
PUBLISHED
Keywords: chemical bonding, density functional theory, heterolytic scissions, homolytic scissions, nitrile imine